Size Reduction Method for Laboratory Testing in Hot Mix Asphalt - Delbono, Hector Luis (2025)
In a multilayer system, as a pavement with layers of different materials, movements between layers are an important source of cracks. When the adhesion between layers is poor, often cracking appear early with increasing deformation at the loads of traffic due to consumption of internal energy of the material, causing problems fatigue cracks from top to bottom (top- down). In this context the study of adherence between different substrates (base concrete and asphalt base), interposing different geosynthetic materials, using as a bonding agent a modified asphalt emulsion, and placing thereon a layer of conventional asphalt CAC D20, acting as reinforcement in rehabilitating deteriorated of pavements was proposed. It is considered as a reference intercoat adhesion without placing any geosynthetic material. To quantify the adhesion it was used strength test cut LCB (Laboratorio de Caminos de Barcelona), and the adhesion test traction implemented in the LEMaC, Highway Research Center of the National Technological University of La Plata is used. The load and deformation at the interfase of materials, were tested and a result it was observed that adhesion is favorably or unfavorably affected, depending on the type of geosynthetic material and the substrate where it is applied.